Improvement of Catalytic Water Oxidation on MnOx Films by Heat Treatment. Issue 4 (4th March 2013) - Zhou, Fengling; Izgorodin, Alex; Hocking, Rosalie K.; Armel, Vanessa; Spiccia, Leone; MacFarlane, Douglas R.
Abstract Manganese oxides (MnOx) are considered to be promising catalysts for water oxidation. Electrodeposited MnOx films from aqueous electrolytes have previously been shown to exhibit a lower catalytic action than films deposited from ionic liquids when tested in strongly alkaline conditions. In this study, we describe a thermal treatment that converts the MnOx films deposited from aqueous electrolytes to highly catalytic films with comparable activity to ionic‐liquid‐deposited films. The films deposited from aqueous electrolytes show a remarkable improvement in the catalysis of water oxidation after heat treatment at a low temperature (≤120 °C) for 30 min. The films were characterised by using XRD and SEM, and energy‐dispersive X‐ray (EDX), FTIR and Raman spectroscopy, which indicate that dehydration occurs during the heat treatment without significant change to the microstructure or bulk composition. The X‐ray absorption spectroscopy (XAS) results show the growth of small amounts (ca. 3–10 %) of reduced Mn species (MnII or MnIII) after heat treatment. The dehydration process removes structural water and hydroxyl species to result in a conductivity improvement and a more active catalyst, thereby contributing to the enhancement in water oxidation performance.